(untitled) (Journal of Engineering, 2009)
A two-dimensional depth-averaged hydrodynamic model and a two-dimensional water quality parameters transport model were developed to simulate the characteristics of Al Huwayza Marsh, which is considered the largest and most important marsh in the south of Iraq. The hydrodynamic model for Al Huwayza Marsh was built by using RMA2 model, while the water quality model was built by using RMA4 model. These two models are part of Surface Water Modeling System, SMS, software package. To investigate the effect of the marsh boundary configuration on the variation of the velocity pattern and the water quality within the marsh, both of the hydrodynamic and the water quality models were applied to three cases of boundary configuration of Al Huwayza Marsh. The first case represents the natural extension of the marsh boundary. The second case represents the existing boundary configuration of the marsh, in which the south west of the marsh is bounded by a dyke. The third case represents the Iraqi part of the marsh bounded by the south west dyke and a dyke along the Iraq-Iranian borders, which when completed will separate the marsh into two parts. Models runs were based on above cases of Al Huwayza Marsh boundary configuration and topographical survey, hydrological measurements and routing, and water quality measurements carried out by the Center of Rehabilitation of Iraqi Marshlands. Discharges of all feeders and stages of the outlets are considered for wet, normal, and dry years. Feeder’s seasonal discharges were averaged. High and low concentrations of three selected water quality parameters of the marsh feeders were adopted in the model runs. Generally, it was found that the flow velocities are relatively high at the inlets and outlets of the marsh. The construction of the dyke along the Iraqi-Iranian border leads to variation in the direction of water flow in all portions of the marsh and a great reduction in AsSuwayb River discharge. While, a slight effect was noticed in the mixing process of the feeders’ water of different concentration in case three compared to other cases